2021
DOI: 10.3390/jcm10091992
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Rheumatic Diseases: An Update on the Role of Atherogenic Electronegative LDL and Potential Therapeutic Strategies

Abstract: Atherosclerosis has been linked with an increased risk of atherosclerotic cardiovascular disease (ASCVD). Autoimmune rheumatic diseases (AIRDs) are associated with accelerated atherosclerosis and ASCVD. However, the mechanisms underlying the high ASCVD burden in patients with AIRDs cannot be explained only by conventional risk factors despite disease-specific factors and chronic inflammation. Nevertheless, the normal levels of plasma low-density lipoprotein (LDL) cholesterol observed in most patients with AIRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 132 publications
0
4
0
Order By: Relevance
“…Four blood lipids-TC, TG, LDL-C, and HDL-C-are important indicators used to reveal changes in blood lipids (Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four blood lipids-TC, TG, LDL-C, and HDL-C-are important indicators used to reveal changes in blood lipids (Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, obesity somewhat correlates with lipid disorders. Four blood lipids—TC, TG, LDL‐C, and HDL‐C—are important indicators used to reveal changes in blood lipids (Chen et al, 2021 ). Earlier studies showed that HDL‐C levels negatively correlate with carotid atherosclerosis progression (Hedayatnia et al, 2020 ; Teis et al, 2021 ), while higher LDL‐C levels and lower HDL‐C levels might correlate with cardiovascular diseases (CVDs) such as stroke (Zhang, Wei, et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with T2D are prone to osteoporosis, which further increases the probability of fractures ( 6 ). High blood glucose levels can lead to the development of atherosclerotic cardiovascular disease in the blood vessels, affecting the quality and duration of patient survival ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is the leading non-communicable chronic disease cause of death worldwide (Mendis, 2017; Zhao et al, 2019). Rheumatic disease (RD), a life-threating disease that affects 11.6%–46.4% of the adult population (American College of Rheumatology [ACR], 2023; Zeng et al, 2008) increases the risk of premature atherosclerosis CVD in sufferers and imposes high burdens on individuals, families, and healthcare resources (Chen et al, 2021; Mahtta et al, 2020; Rahman et al, 2013). RD encompasses over 200 distinct rheumatologic conditions characterized by pain and reduced mobility and physical function in one or more areas of the musculoskeletal system.…”
mentioning
confidence: 99%